2021
DOI: 10.4314/sajas.v51i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mentha on performance, haematological and biochemical parameters in laying hens

Abstract: Effects of Mentha piperita (peppermint) extract and juice on performance and immune parameters were evaluated in laying hens. A total of 252 Babcock laying hens were allocated to seven treatments with four replications of nine hens. The control hens were fed a basal diet without supplementation. Other hens were given diets supplemented with mentha extract (ME) at 50 (50ME), 100 (100ME), and 200 (200ME) mg/kg of feed or with 50 mentha juice (50MJ), 100 (100MJ) and 200 (200MJ) mg/L that was provided in the drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Beneficial effects on productive performance and egg quality were obtained by supplementing the laying hen’s diet with Pinus massoniana [ 40 ], Curcuma longa [ 32 ], Geranium thunbergia , and Mentha arvensi [ 42 ]. However, egg production, FCR, and egg weight were not increased with the addition of dietary Thymus vulgaris L. [ 43 ] and Mentha piperita [ 8 ]. Sharma et al [ 6 ] stated that the administration of garlic and thyme to the diets of laying hens did not increase egg weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beneficial effects on productive performance and egg quality were obtained by supplementing the laying hen’s diet with Pinus massoniana [ 40 ], Curcuma longa [ 32 ], Geranium thunbergia , and Mentha arvensi [ 42 ]. However, egg production, FCR, and egg weight were not increased with the addition of dietary Thymus vulgaris L. [ 43 ] and Mentha piperita [ 8 ]. Sharma et al [ 6 ] stated that the administration of garlic and thyme to the diets of laying hens did not increase egg weight.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have also discovered a negligible effect of phytogenic extracts supplementation on the productive parameters or egg quality [ 5 , 6 ]. On the other hand, they may only produce a negative impact on poultry when added to diets at high levels [ 7 , 8 ]. For instance, a phenolic group such as tannins exhibits anti-nutritional properties at high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that 296 mg/kg of peppermint oil positively affected feed intake, egg production, and the conversion ratio of laying hens (Abdel-Wareth and Lohakare, 2020 ), whereas, in the present study, we found that dietary PE supplementation could improve egg production but did not affect the feed efficiency of laying hens during the late-phase laying period. Rahman et al ( 2021 ) also revealed that an ethanolic extract of peppermint had no detectable differences in the feed conversion ratio of laying hens. Our findings indicated that dietary PE supplementation of 0.30 and 0.37% was required for optimal laying performance in late-phase laying hens.…”
Section: Discussionmentioning
confidence: 96%
“…Studies on the effect of peppermint on the production of eggs have been reported by several workers (Rahman et al 2021;Abdel-Wareth and Lohakare 2020). Supplementation of the diets with peppermint up to 3% did not increase hen day production and egg mass in the present study.…”
Section: Effect Of Peppermint Leaves Meal On Egg Productionmentioning
confidence: 99%
“…The effects of peppermint on egg quality have been studied by several workers (Centigul et al 2008;Rahman et al 2021;Abdel-Wareth and Lohakare 2020). Lower yolk height, albumen height, and HU found in the eggs produced by laying hens in the current study indicate that eggs underwent biochemical and physical changes when they were stored at room temperature for 2 weeks.…”
Section: Effects Of Peppermint Leaf Meal On Egg Qualitymentioning
confidence: 99%